Pengaruh Media Pembelajaran Powtoon, Disiplin Belajar dan Lingkungan Belajar Terhadap Hasil Belajar Akuntansi Keuangan Dimasa Pandemi Covid-19 - Anik Novitasari; Vivi Pratiwi (Jurnal Pendidikan Akuntansi (JPAK), 2022)
This study aims to analyze the effects of PowToon learning media, discipline and learning environment partially or simultaneously with learning learning results. This study uses a quantitative approach with 61 population students. The specified sample method is saturated sampling. Data was collected by a questionnaire. Data analysis with multiple linear regressions. The results of the survey conclude that: (1) The important effect of Powtoon learning media on financial accounting learning outcomes is the result of t count = 3.184> ttable = 2.002. (2) In the result of t count = 2,650> t table = 2,002, the learning outcome of financial accounting has an important influence of learning discipline. (3) In the result of t count = 3.136> t table = 2.002, the learning outcome of financial accounting has a great influence on the learning environment. (4) Powtoon learning media, learning discipline, and learning environment have a great influence on the learning outcomes of financial accounting, as well as the results of Fcount> Ftable, ie 4.908> 2.76.